Deskripsi Pelaku Perundungan pada Anak Usia Didik Sebagai Isu Psikologi Sosial di Indonesia - Charles Petra Nicolaas Rembang (EUANGGELION: Jurnal Teologi dan Pendidikan Kristen, 2023)
Abstract: Bullying is an effort or action carried out by individual human beings, both personally and collectively that attacks a target repeatedly physically, psychologically, socially or verbally, which is carried out in a situationally defined position of strength for their own benefit or satisfaction (Elinda Emza, 2015). Another opinion defines bullying as the use of aggression in any form that aims to hurt or corner other people physically or mentally.Purpose: To describe and explain the perpetrators of bullying in school-aged children as a social psychological issue in Indonesia. In terms of (1) the perpetrators of bullying, (2) the causes of bullying, (3) the process of bullying behavior, (4) excesses of bullying behavior. Methodology: This research is a research with a descriptive qualitative approach, namely a research method that utilizes qualitative data which is described according to the existing conditions and facts. Descriptive method is a method in examining the status of human groups, an object, condition, a system of thought or a class of events in the present. The strength of this method lies in the facts that are happening now. Data collection by means of interviews, journals, digital books, mainstream media such as mass media, social media (XL nodes), libraries, data agencies or organizations. Data Collection Techniques use the Fishbone Technique, which emphasizes collecting data from various sources and collectors. The data analysis technique uses the Morphology Technique, which is a technique that describes the quality of a problem that explains it comprehensively.Implication: Bullying in Student Age Children as a Social Psychological Issue is a reality whose phenomenon occurs everywhere. In the case of perpetrators of bullying, this is a big problem that must be handled together. Data on bullying in Indonesia, especially on students in their teens, is still very high. The perpetrators of bullying continue to carry out their actions because there are still many reproaches that are open to repetition. Students are the main perpetrators of bullying on other students. Teachers, parents and the community either directly or indirectly have played a role in bullying. The process of bullying; Social media is the most powerful tool for perpetrators of bullying that can continue in the real world. Educational institutions and systems do not clearly handle cases of bullying, especially for perpetrators. The government and schools have not been firm in terms of bullying rules and laws. The perpetrator commits bullying in verbal and non-verbal ways. Causes of bullying behavior; there are problems that arise from the perpetrator who is mentally unstable; Another cause is the existence of problems in the social psychology of society which indirectly help perpetrators commit bullying. The excesses of bullying behavior include: The excesses for the bully are legal issues, negotiations, revenge and repetition of acts that can turn them into criminals, radicals and terrorists. Victims of bullying can become perpetrators in the future. If the perpetrators of bullying are not prevented, they can become predators for the next victims. That bullying is a behavior that can be modified through the education process.